Obnova objektů a rekultivace území, Portlaw - Kuběna, Martin (Vysoké učení technické v Brně. Fakulta architektury, 2024)
Cílem práce je vytvořit místo, které bude spojovat výzkum, vzdělání a popularizaci z oblasti environmentální problematiky a dále ji předávat a vysvětlovat široké veřejnosti v podobě přednášek, publikací a osvětově kulturních akcí. Bude se zabývat laboratorním výzkumem kontaminantů a složení kontaminované půdy, přírodní sukcesí a krokům k předejití znehodnocení půdy při výrobních a jiných procesech. Akce pořádané v areálu budou zaměřeny nejen na turisty a návštěvníky přijíždějící do areálu po cyklostezce nebo na místní obyvatele a jejich přátele, ale také na širší publikum ve formě konferencí a auditů na téma kontaminace a environmentu.

The goal of the work is to create a place that will combine research, education and popularization in the field of environmental issues and further convey and explain it to the general public in the form of lectures, publications and educational and cultural events. It will deal with laboratory research on contaminants and the composition of contaminated soil, natural succession and steps to prevent soil degradation during production and other processes. The events organized in the area will be aimed not only at tourists and visitors coming to the area via the cycle path or at local residents and their friends, but also at a wider audience in the form of conferences and audits on the topic of contamination and the environment.
Refurbishment and conversion of former factory, Portlaw
Keywords: Irsko; Portlaw; rekonverze; environment; Ireland; Portlaw; reconverison; environment